Government Policy: Change And Preservation Of Isan Culture - et. al., Chanchai Huadsri, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objectives of research were; 1) to analyze the changes and preservation of Isan culture in politics and government through policies of government and constitution, 2) to analyze political and government changes affected Isan culture, and 3) analyze integration of Isan culture and government politics. This is a qualitative research by collecting information from documents in-depth interviews and participatory observation. There are 45 key informants consisting of; 1) 15 government representatives, 2) 15 persons from local government organization, and 3) 15 local scholars as being both monks and laity. The research results were found that; 1. The change and preservation of Isan culture is the result of changes under government policy, which can be determined by the Constitutional Law and the plan of National Economic and Social Development. It starts with developing people by using culture as the base of development. And then local wisdom and culture were applied to create the value of the product based on knowledge and Thai in order to drive to the growth from increasing productivity based on wisdom and innovation. 2. Thai society at the present time has progressed in technology development. The rapid change in all dimensions both social, economic, political and technological was for creating a cultural development plan according to the 20-year national strategy and the directional framework under the policy of development to Thailand 4.0. 3. The integration of Isan culture and government politics is the result of government policies emphasized the participation of all sectors in society and focused on "People-Centered Development" by transforming the development methods into holistic integration. There is a blend of culture and government policies to make income for the community through cultural tourism activities due to the participation of people within that community under the support of government agencies and the private sectors through various activities.